Exploring the immunomodulatory role of virtual memory CD8+ T cells: Role of IFN gamma in tumor growth control - Savid-Frontera, Constanza; Viano, Maria Estefania; Baez, Natalia S.; Lidon, Nicolas L.; Fontaine, Quentin; Young, Howard A.; Vimeux, Lene; Donnadieu, Emmanuel; Rodriguez-Galan, Maria Cecilia (Frontiers in Immunology, 2022)
Virtual memory CD8+ T cells (TVM) have been described as cells with a memory-like phenotype but without previous antigen (Ag) exposure. TVM cells have the ability to respond better to innate stimuli rather than by TCR engagement, producing large amounts of interferon gamma (IFN) after stimulation with interleukin (IL)-12 plus IL-18. As a result of the phenotypic similarity, TVM cells have been erroneously included in the central memory T cell subset for many years. However, they can now be discriminated via the CD49d receptor, which is up-regulated only on conventional memory T cells (TMEM) and effector T cells (TEFF) after specific cognate Ag recognition by a TCR. In this work we show that systemic expression of IL-12 plus IL-18 induced an alteration in the normal TVM vs TMEM/TEFF distribution in secondary lymphoid organs and a preferential enrichment of TVM cells in the melanoma (B16) and the pancreatic ductal adenocarcinoma (KPC) tumor models. Using our KPC bearing OT-I mouse model, we observed a significant increase in CD8+ T cell infiltrating the tumor islets after IL-12+IL-18 stimulation with a lower average speed when compared to those from control mice. This finding indicates a stronger interaction of T cells with tumor cells after cytokine stimulation. These results correlate with a significant reduction in tumor size in both tumor models in IL-12+IL-18-treated OT-I mice compared to control OT-I mice. Interestingly, the absence of IFN completely abolished the high antitumor capacity induced by IL-12+IL-18 expression, indicating an important role for these cytokines in early tumor growth control. Thus, our studies provide significant new information that indicates an important role of TVM cells in the immune response against cancer.